2022
DOI: 10.1186/s12969-022-00723-5
|View full text |Cite|
|
Sign up to set email alerts
|

Successful rituximab treatment for severe rapidly progressive interstitial lung disease with anti-MDA5 antibody-positive juvenile dermatomyositis: a case report and literature review

Abstract: Background Rapidly progressive (RP) interstitial lung disease (ILD) is a life-threatening complication of juvenile dermatomyositis (JDM); however, it is generally refractory to treatment; to the best of our knowledge, no evidence-based treatment has been established for RP-ILD yet. We present the case of a 2-year-old girl with RP-ILD who showed resistance to treatment with methylprednisolone, cyclosporine A, cyclophosphamide, immunoglobulin, and plasma exchange (PE) and was finally treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, when CADM with RP-ILD is suspected, intensive immunosuppressive therapy should be started before a definitive diagnosis with the responsible autoantibody. Although additional treatments, such as mycophenolate mofetil or rituximab administration, should be considered in a refractory case against intensive immunosuppression, there is currently no established treatment [21,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when CADM with RP-ILD is suspected, intensive immunosuppressive therapy should be started before a definitive diagnosis with the responsible autoantibody. Although additional treatments, such as mycophenolate mofetil or rituximab administration, should be considered in a refractory case against intensive immunosuppression, there is currently no established treatment [21,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that cyclophosphamide (CYC) is more effective for refractory skin lesions, while rituximab (RTX) in combination with immunosuppressants is beneficial for those with combined RP-ILD. [23][24][25] A recent retrospective study indicated that 71.43% (25/35) of patients with anti-MDA5 DM responded to RTX treatment for ILD, with more than half experiencing improvement in skin rashes. However, 37.14% of patients developed infections after RTX use.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis is often awaited to start more specific medications such as corticosteroids, azithromycin, hydroxychloroquine or anti-fibrosing therapies [103][104][105][106][107][108][109][110][111][112]. In chILD related to connective tissue diseases or autoinflammatory syndromes, immunosuppressive drugs such as mycophenolate mofetil, azathioprine, rituximab or Janus kinase inhibitors may be discussed [96,97,[113][114][115][116].…”
Section: Lung Biopsymentioning
confidence: 99%